Pumpless Extracorporeal Hemadsorption Technique (pEHAT): a proof-of-concept animal study - Fiedler-Kalenka, Mascha; Muellenbach, Ralf M.; Rolfes, Caroline; Lotz, Christopher; Nickel, Felix; Müller, Beat P.; Supady, Alexander; Lepper, Philipp Moritz; Weigand, Markus A.; Meybohm, Patrick; Kalenka, Armin; Reyher, Christian (Journal of Clinical Medicine, 2022)
Background: Extracorporeal hemadsorption eliminates proinflammatory mediators in critically ill patients with hyperinflammation. The use of a pumpless extracorporeal hemadsorption technique allows its early usage prior to organ failure and the need for an additional medical device. In our animal model, we investigated the feasibility of pumpless extracorporeal hemadsorption over a wide range of mean arterial pressures (MAP). Methods: An arteriovenous shunt between the femoral artery and femoral vein was established in eight pigs. The hemadsorption devices were inserted into the shunt circulation; four pigs received CytoSorb® and four Oxiris® hemadsorbers. Extracorporeal blood flow was measured in a range between mean arterial pressures of 45-85 mmHg. Mean arterial pressures were preset using intravenous infusions of noradrenaline, urapidil, or increased sedatives. Results: Extracorporeal blood flows remained well above the minimum flows recommended by the manufacturers throughout all MAP steps for both devices. Linear regression resulted in CytoSorb® blood flow [mL/min] = 4.226 × MAP [mmHg] − 3.496 (R-square 0.8133) and Oxiris® blood flow [mL/min] = 3.267 × MAP [mmHg] + 57.63 (R-square 0.8708), respectively. Conclusion: Arteriovenous pumpless extracorporeal hemadsorption resulted in sufficient blood flows through both the CytoSorb® and Oxiris® devices over a wide range of mean arterial blood pressures and is likely an intriguing therapeutic option in the early phase of septic shock or hyperinflammatory syndromes.
Gesehen am 31.01.2023